dBcAMP Rescues the Neurons From Degeneration in Kainic Acid-Injured Hippocampus, Enhances Neurogenesis, Learning, and Memory - Rao, Muddanna Sakkattu; Abd-El-Basset, Ebtesam M. (Frontiers in Behavioral Neuroscience, 2020)
Dibutyryl cyclic adenosine monophosphate (dBcAMP) is a cell-permeable synthetic analog of cyclic adenosine monophosphate (cAMP). Although the elevation of cAMP levels was reported to promote the functional recovery in spinal cord injury, its role in neurogenesis or functional recovery after hippocampal injury is unknown. The objective of the study was to investigate the effects of dBcAMP on learning, memory, and hippocampal neurogenesis in the excitotoxically lesioned hippocampus. An excitotoxic lesion was induced in the hippocampi of 4-month-old male BALB/c mice by injecting 0.25 μg/μl into the lateral ventricles of both sides. The lesioned mice (L) were divided into L+dBcAMP and L+phosphate-buffered saline (PBS) groups. Sham surgery (S) was done by the injection of 1 μl of sterile saline into the lateral ventricles. The sham surgery mice were divided into S+dBcAMP and S+PBS groups. Mice in the L+dBcAMP and S+dBcAMP groups were treated with dBcAMP for 1 week (i.p., 50 mg/kg), whereas mice in the L+PBS and S+PBS groups were treated with PBS. The mice in all groups were subjected to water maze and passive avoidance tests at the end of the 4th week. Cresyl violet staining and NeuN and doublecortin immunostaining were done to analyze the morphology and neurogenesis. The water maze learning sessions did not show a significant difference in escape latency between the groups, suggesting an unimpaired learning ability of mice in all groups. The L+dBcAMP mice had significantly short entry latency and higher target quadrant time/distance traveled compared to the L+PBS group, suggesting better memory retention. The L+dBcAMP group had a significantly improved memory retention compared to the L+PBS mice during the passive avoidance test. Morphological studies showed significantly greater adult neurons and increased hippocampal neurogenesis in the hippocampus of mice in the L+dBcAMP group compared to those in the L+PBS group. There was no significant difference between the S+dBcAMP and S+PBS groups in the water maze/passive avoidance tests and the number of neurons. In conclusion, dBcAMP protects the hippocampal neuron from degeneration and enhances hippocampal neurogenesis, learning, and memory.